Extent, pattern and risk factors of alcohol and tobacco use among undergraduate students in a university in Kathmandu: A cross-sectional study - Shah, Archana; Shah, Bigya; Mishra, Rajan; Sah, Ajit Kumar; Shrestha, Eloma; Choulagai, Bishnu P (Journal of Psychiatrists’ Association of Nepal, 2022)
Correction: Several tables were omitted from this article by mistake. The correct PDF was loaded on 23/08/2023. Background: Alcohol and tobacco use disproportionately affect young people and can lead to significant morbidity and mortality. High-risk factors often begin during adolescence and there is a long interval between exposure and disease development. This study aims to examine the prevalence and patterns of alcohol and tobacco use among undergraduates and to identify the risk factors associated with their use. Methods and Materials: A structured self-administered web-based questionnaire using a cross-sectional design and stratified proportionate sampling was conducted. The questionnaire was based on the World Health Organization’s (WHO) Stepwise approach to surveillance of risk factors. The data was analyzed using SPSS version 25. Results: Proportion of male and female participants was nearly equal. One-tenth of the participants were current tobacco users with cigarettes being the most used tobacco product while more than one-fourth currently consumed alcohol. Males were associated with lifetime alcohol and tobacco use, as well as current tobacco use. Senior-year students had a significant association with lifetime alcohol use, while insufficient intake of fruits and vegetables was associated with current alcohol use. Additionally, non-medical campus and junior-year students were associated with current tobacco use. Conclusion: Alcohol and tobacco use among undergraduate students in a Kathmandu university show serious concern. Health professionals, faculty, stakeholders, and policymakers should take note of these findings and design interventions to promote the mental and physical health of young people and prevent addictive disorders.